Freestanding CoSeO3·H2O nanoribbon/carbon nanotube composite paper for 2.4 V high-voltage, flexible, solid-state supercapacitors. Issue 25 (15th June 2018) - Jiang, Yingchang; Wu, Zeyi; Jiang, Le; Pan, Zhichang; Yang, Peiyu; Tian, Wenchao; Hu, Linfeng
Abstract : Freestanding paper consisting of ultrathin CoSeO3 ·H2 O nanoribbons and carbon nanotubes fabricated by a vacuum-assisted filtration strategy exhibits 2.4 V high-voltage, high energy density and excellent flexibility for solid-state supercapacitors. Abstract : The integration of high flexibility, high energy density and wide voltage window for solid-state supercapacitors remains a big challenge to date. Herein, ultrathin CoSeO3 ·H2 O nanoribbons (thickness: ∼14 nm) with typical pseudocapacitive behavior were synthesized in a high yield by a solution-based refluxing process. Freestanding CoSeO3 ·H2 O ribbon/hydroxylated multi-walled carbon nanotube (HWCNT) paper could be fabricated through a vacuum-assisted filtration strategy owing to its ultrathin nature, ribbon-like morphology and inherent flexibility. Unexpectedly, an asymmetric supercapacitor constructed from this as-prepared CoSeO3 ·H2 O/HWCNT hybrid paper exhibits a high 2.4 V voltage window as well as excellent rate capability and cycle performance. The energy density of this device is 132.3 W h kg −1 at 960 W kg −1 with a stable cycling ability of up to 10 000 cycles, which is superior to those of almost all previously reported asymmetric supercapacitors based on freestanding paper. Furthermore, this supercapacitor shows outstanding bendability and mechanical stability at different bending degrees from 0° to 180° with no changes in capacitive behavior. Our work provides new opportunities for developing high-performance asymmetric supercapacitors with high energy density, wide voltage window, and high flexibility in a novel CoSeO3 ·H2 O system for potential applications including flexible displays, collapsible mobile phones, and wearable equipment.